Size‐Dependent Electroporation of Dye‐Loaded Polymer Nanoparticles for Efficient and Safe Intracellular Delivery. Issue 2 (18th December 2020) - Egloff, Sylvie; Runser, Anne; Klymchenko, Andrey; Reisch, Andreas
Abstract: Efficient and safe delivery of nanoparticles (NPs) into the cytosol of living cells constitutes a major methodological challenge in bio‐nanotechnology. Electroporation allows direct transfer of NPs into the cytosol by forming transient pores in the cell membrane, but it is criticized for invasiveness, and the applicable particle sizes are not well defined. Here, in order to establish principles for efficient delivery of NPs into the cytosol with minimal cytotoxicity, the influence of the size of NPs on their electroporation and intracellular behavior is investigated. For this study, fluorescent dye‐loaded polymer NPs with core sizes between 10 and 40 nm are prepared. Optimizing the electroporation protocol allows minimizing contributions of endocytosis and to study directly the effect of NP size on electroporation. NPs of <20 nm hydrodynamic size are efficiently delivered into the cytosol, whereas this is not the case for NPs of >30 nm. Moreover, only particles of core size <15 nm diffuse freely throughout the cytosol. While electroporation at excessive electric fields induces cytotoxicity, the use of small NPs <20 nm allows efficient delivery at mild electroporation conditions. These results give clear methodological and design guidelines for the safe delivery of NPs for intracellular applications. Abstract : The influence of the size of nanoparticles (NPs) on their efficient and safe delivery through electroporation is studied using dye‐loaded polymer NPs. Only NPs below a threshold hydrodynamic diameter of 20–30 nm can be delivered efficiently. Further decreasing the size to less than 15 nm allows applying particularly mild electroporation conditions.